Microbial adaptation in vertical soil profiles contaminated by an antimony smelting plant. Issue 11 (23rd September 2020) - Xu, Rui; Sun, Xiaoxu; Lin, Hanzhi; Han, Feng; Xiao, Enzong; Li, Baoqin; Qiu, Lang; Song, Benru; Yang, Zhaohui; Sun, Weimin
ABSTRACT: Antimony mining has resulted in considerable pollution to the soil environment. Although studies on antinomy contamination have been conducted, its effects on vertical soil profiles and depth-resolved microbial communities remain unknown. The current study selected three vertical soil profiles (0–2 m) from the world's largest antimony mining area to characterize the depth-resolved soil microbiota and investigate the effects of mining contamination on microbial adaptation. Results demonstrated that contaminated soil profiles showed distinct depth-resolved effects when compared to uncontaminated soil profiles. As soil depth increased, the concentrations of antimony and arsenic gradually declined in the contaminated soil profiles. Acidobacteria, Chloroflexi, Proteobacteria and Thaumarchaeota were the most variable phyla from surface to deep soil. The co-occurrence networks were loosely connected in surface soil, but obviously recovered and were well-connected in deep soil. The metagenomic results indicated that microbial metabolic potential also changed with soil depth. Genes encoding C metabolism pathways were negatively correlated with antimony and arsenic concentrations. Abundances of arsenic-related genes were enriched by severe contamination, but reduced with soil depth. Overall, soil depth-resolved characteristics are often many meters deep and such effects affected the indigenous microbial communities, as well as their metabolic potential due to different contaminants along vertical depths. Abstract : Results indicated that microbial adaptation changed in response to different levels of contamination throughout the soil profiles, which were distinct from the control profile.